Characteristic length scales and time‐averaged transport velocities of suspended sediment in the mid‐Atlantic Region, USA. Issue 2 (3rd February 2014) - Pizzuto, James; Schenk, Edward R.; Hupp, Cliff R.; Gellis, Allen; Noe, Greg; Williamson, Elyse; Karwan, Diana L.; O'Neal, Michael; Marquard, Julia; Aalto, Rolf; Newbold, Denis
<x xml:space="preserve">Abstract</x> [1] Watershed Best Management Practices (BMPs) are often designed to reduce loading from particle‐borne contaminants, but the temporal lag between BMP implementation and improvement in receiving water quality is difficult to assess because particles are only moved downstream episodically, resting for long periods in storage between transport events. A theory is developed that describes the downstream movement of suspended sediment particles accounting for the time particles spend in storage given sediment budget data (by grain size fraction) and information on particle transit times through storage reservoirs. The theory is used to define a suspended sediment transport length scale that describes how far particles are carried during transport events, and to estimate a downstream particle velocity that includes time spent in storage. At 5 upland watersheds of the mid‐Atlantic region, transport length scales for silt‐clay range from 4 to 60 km, while those for sand range from 0.4 to 113 km. Mean sediment velocities for silt‐clay range from 0.0072 km/yr to 0.12 km/yr, while those for sand range from 0.0008 km/yr to 0.20 km/yr, 4–6 orders of magnitude slower than the velocity of water in the channel. These results suggest lag times of 100–1000 years between BMP implementation and effectiveness in receiving waters such as the Chesapeake Bay (where BMPs are located upstream of the characteristic transport length scale). Many particles likely travel much faster than these average values, so further research is needed to determine the complete distribution of suspended sediment velocities in real watersheds.